2019
DOI: 10.1098/rsos.190771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic matters on anammox coupled denitrification system: when nitrite was sufficient

Abstract: Anaerobic ammonia oxidation (anammox) and denitrification can work together to weaken the influence of organic matter on anaerobic ammonia oxidation bacteria (AAOB) and improve nitrogen removal performance. As the common substrate of anammox and denitrification, nitrite will also affect nitrogen removal performance when it is insufficient, which is not conducive to reflect the endurance of anammox reactor to organic matter. The UASB continuous flow experiment was carried out to investigate the effect of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The relative abundance of Thauera was not significantly different in both filters ( p = 0.39) (Figure 3). In addition, the most predominant genera found in both filters (an uncultured bacterium from the Burkholderiaceae family and Aquabacterium ) have also been observed in PdNA systems (Yang et al, 2019, 2021). Aquabacterium was however significantly more abundant in the expanded clay filter than in the sand filter ( p < 0.005) (Figure 3).…”
Section: Resultsmentioning
confidence: 94%
“…The relative abundance of Thauera was not significantly different in both filters ( p = 0.39) (Figure 3). In addition, the most predominant genera found in both filters (an uncultured bacterium from the Burkholderiaceae family and Aquabacterium ) have also been observed in PdNA systems (Yang et al, 2019, 2021). Aquabacterium was however significantly more abundant in the expanded clay filter than in the sand filter ( p < 0.005) (Figure 3).…”
Section: Resultsmentioning
confidence: 94%
“…Relative abundance throughout the study of (a) anammox species and SM1A02 identified before to be related to mainstream anammox (Tian et al, 2017; Vico et al, 2021; Xin et al, 2023), (b) denitrifiers recognized to be well suited for partial denitrification according to previous studies (Campoloong et al, 2019; Du, Cao, Li, et al, 2017, 2019; Du et al, 2016; Fofana, Huynh et al, 2022; He et al, 2018; B. Liu et al, 2013; Osaka et al, 2006; D. Wang et al, 2020; J. Yang et al, 2019; B. Ma et al, 2020; Z.‐B. Wang et al, 2021; Martineau et al, 2015; Zhan et al, 2020; Y. Yang et al, 2021), (c) methylotrophs and (d) DEMON seed compostion used for bioaugmentation of the pilot.…”
Section: Resultsmentioning
confidence: 86%
“…Molecular analysis offered an insight into which species or genera of microorganisms were critical for PdN selection. Thauera , a denitrifier identified in many PdN systems (Du et al, 2016; Du, Cao, Li, et al, 2017, 2019; Fofana, Huynh, et al, 2022; He et al, 2018; Liu et al, 2013; Osaka et al, 2006; Wang et al, 2020; Yang et al, 2019), was a dominant species in this system (Figure 6b) and most likely responsible for PdN. This is because its relative abundance had a similar trend with the system's PdN efficiency (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment of anammox bacteria has previously been observed in nitrate‐reducing benzene‐degrading cultures (Atashgahi et al, 2018; Han et al, 2020; Luo et al, 2014; Melkonian et al, 2021; Peng et al, 2017) and also a nitrate‐reducing cyclohexane‐degrading enrichment culture (Musat et al, 2010), and some of these studies revealed that the presence of anammox bacteria can increase nitrate‐dependent benzene degradation rates indicating anammox bacteria might detoxify nitrite (Han et al, 2020; Peng et al, 2017). Yang et al (2019) established that nitrite is a common substrate of anammox and denitrification processes, which affects nitrogen removal performance. Thus, denitrifying and anammox bacteria may be co‐occurring in our system to regulate nitrite concentrations.…”
Section: Discussionmentioning
confidence: 99%